Managing emergencies and crises global perspectives - Kapucu, Naim; Özerdem, Alpaslan; Sadiq, Abdul-Akeem (Jones & Bartlett Learning, 2023)
"As the scale, frequency, and intensity of crises faced by the world have dramatically increased over the last decade, there is a critical need for a careful stocktaking on the knowledge of managing disasters. Managing Emergencies and Crises: Global Perspectives clearly and comprehensively explores the most important concepts of emergency and crisis management, such as mitigation, protection, prevention, preparedness, response, recovery, and vulnerability and risk assessment, and illustrates them with cases involving disasters and emergencies worldwide. Substantially revised, the Second Edition has been reorganized and includes two new and timely chapters on terrorism and emergency management and public health emergencies and crises. It also provides an emphasis on management and leadership and cross-sector governance from interdisciplinary and global perspectivesKey Features:- Two new chapters: Terrorism and Emergency Management and Public Health Emergencies and Crises. - Diverse scholarly perspectives are presented to guide readers' understanding of various concepts in the emergency and crisis management field. - Rich and diverse case studies illustrate how various stakeholders, including emergency program managers, respond in crisis and emergency management situation. - Navigate eBook Access (included with the print text) provides online or offline access to the digital textbook"--